Brief Report: Relationship of Age and Body Mass Index to Skin Temperature and Skin Perfusion in Primary Raynaud's Phenomenon. Issue 1 (January 2015) - Giurgea, Georgiana‐Aura; Mlekusch, Wolfgang; Charwat‐Resl, Silvia; Mueller, Markus; Hammer, Alexandra; Gschwandtner, Michael E.; Koppensteiner, Renate; Schlager, Oliver
<x xml:space="preserve">Abstract</x> Objective To assess the relationship of age and body mass index (BMI) to skin temperature and perfusion in patients with primary Raynaud's phenomenon (RP) compared with controls. Methods Patients with RP as well as age‐ and sex‐matched controls underwent external cold provocation by exposure to 20°C water for 1 minute. Before and after cold provocation, skin temperature and skin perfusion were measured. Results Twenty‐six patients with RP (20 women and 6 men; median age 41.9 years) and 22 controls (17 women and 5 men; median age 42.9 years) were studied. In RP patients, cold exposure led to a median change in skin temperature of −7% (interquartile range [IQR] −13.1, −4.1) and to a median change in skin perfusion of −26.4% (IQR −36.2, 2.9). In controls, skin temperature changed by −15.7% (IQR −18.3, −11.6) and skin perfusion by −33% (IQR −53.3, −1.1) upon cold exposure. In patients with RP, age and BMI were related to skin temperature (for age, r = 0.683, P < 0.0001; for BMI r = 0.657, P < 0.0001) and skin perfusion (for age, r = 0.595, P = 0.002; for BMI, r = 0.653, P < 0.0001), while no association was found in controls. The cold‐induced decrease in skin temperature was inversely related to age (r = −0.518, P = 0.003) and BMI (r = −0.662, P < 0.0001) in patients with RP; correlations were not observed in controls. The cold‐induced change in skin perfusion was not related to age or BMI in either group. Conclusion The cold‐induced decrease in skin temperature is related to age and BMI in patients with RP but not in controls. Further studies are needed to clarify the pathophysiology of digital ischemia in primary RP.